Review of distance education research (2000 to 2008): Analysis of research areas, methods, and authorship patterns - Olaf Zawacki-Richter; Eva Maria Baecker; Sebastian Vogt (International Review of Research in Open and Distributed Learning, 2009)
This paper presents a review of distance education literature to describe the status thereof and to identify gaps and priority areas in distance education research based on a validated classification of research areas. The articles (N = 695) published in five prominent distance education journals between 2000 and 2008 were reviewed for this study. The conclusion is that distance education research is strongly dominated by issues related to instructional design and individual learning processes; whereas, other important areas (e.g., innovation and change management or intercultural aspects of distance learning) are dreadfully neglected. There is a significant trend towards collaborative research and more qualitative studies. Over 80% of all articles originate from only five countries.